Food taxes, farm subsidies and GM crops: new ‘how-to’ guide launched for tailor-made food policies - CGIAR (CGIAR System Organization, 2023)
October 10, WASHINGTON D.C. – A new tool will help governments customise food and agriculture policies based on country-level circumstances to increase their effectiveness at improving diets, adapting to changing climate and protecting natural resources.